Transient infrared nanoscopy resolves the millisecond photoswitching dynamics of single lipid vesicles in water - T. Gölz; E. Baù; J. Zhang; K. Kaltenecker; D. Trauner; S. A. Maier; F. Keilmann; T. Lohmüller; A. Tittl (Nature Communications)
Abstract Understanding the biophysical and biochemical properties of molecular nanocarriers under physiological conditions with minimal interference is critical for advancing photopharmacology, drug delivery, nanotheranostics and synthetic biology. However, analytical methods often struggle to combine precise chemical imaging and dynamic measurements without perturbative labeling. This challenge is exemplified by azobenzene-based photoswitchable lipids, which are intriguing reagents for controlling nanocarrier properties on fast timescales, enabling precise light-induced drug release. Here, we leverage the chemical recognition and high spatio-temporal resolution of scattering-type scanning near-field optical microscopy (s-SNOM) to demonstrate a non-destructive, label-free technique for mid-infrared imaging and spectroscopy of individual photoswitchable liposomes. Our transient nanoscopy approach enables imaging below the diffraction limit and tracks dynamics with sampling times as fast as 30 ms. We resolve photoinduced changes in shape and MIR spectral signature of individual vesicles and discover abrupt and delayed photoisomerization dynamics. Our findings highlight the method’s potential for studying complex dynamics of unlabeled nanoscale soft matter.